THE IMPACT OF CLIMATE CHANGE ON COMMUNAL FARMERS LIVELIHOODS - Nyoni S.R.; Tanale J.; Modiba F.S. (Russian Journal of Agricultural and Socio-Economic Sciences, 2022)
The issues of global warming continue to affect everyone globally. These effects are observed in the changing climate patterns. Since the agricultural sector is not immune to the effects, this study is responding to the climate changes affecting this sector, focusing on Africa. The study aims to explore the effects of climate change on farmers' livelihoods. The study employed an interpretivist paradigm within the qualitative research, using semi-structured interviews to collect data from farmers in Insiza District in Zimbabwe. The findings revealed that most farmers' means of livelihood are from resource-based activities (e.g., farming, fishing, and mineral extraction), and they need to take care of the available natural resources. Additionally, financial capital is the least available asset to the farmers, making it hard for them to achieve their desired outcomes. Farmers had access to land; however, financial constraints and weather conditions affected their envisioned capacity. Nevertheless, adaptive strategies such as irrigation and conservation farming were adopted to manage their challenges. Reflecting on the evidence, farmers have learnt to farm all year round with no fixed seasons due to inconsistent climate patterns. In the past, farmers survived with one income stream, income stream, but climate change has introduced a notion of diversifying income streams to make ends meet.